RESEARCH ON BUYERS' ATTITUDES TOWARDS THE USE OF SOLAR PANELS IN HOUSEHOLDS IN THE REPUBLIC OF SERBIA - Nikolić Ristić, Dragana; Đokić, Nenad (International Journal of Economic Practice and Policy, 2021)
Summary: In modern living, the concept of sustainable development is one of the current topics of research. In this context, the focus on greater use of renewable energy sources is supported in all EU Member States so as in the Republic of Serbia. The aim of this paper is to investigate the attitudes of buyers towards the use of renewable energy sources, especialy solar panels. The first part of the paper provides an overview of scientific literature, while the second part contains the results of a survey of buyers’ attitudes in the Republic of Serbia towards solar panels. The importance of the paper is in the analysis and presentation of buyers’ attitudes towards solar panels in the context of their sociodemographic characteristics.Keywords: sustainable development, renewable energy sources, solar panels, households, buyers’ attitudes, sociodemographic characteristics of buyers, Republic of Serbia.